Vancomycin dosage and its association with clinical outcomes in pediatric patients with gram-positive bacterial infections - Shin, Sooyoung; Jung, Hyun Joo; Jeon, Sang Min; Park, Young Joon; Chae, Jung Woo; Yun, Hwi Yeol (Risk Management and Healthcare Policy, 2020)
Aim: The aim of this study was to evaluate whether vancomycin trough concentrations at initial steady state are associated with clinical and microbiological outcomes along with vancomycin-related nephrotoxicity in pediatric patients with Gram-positive bacterial (GPB) infections. Methods: A retrospective cohort study of pediatric patients who received vancomycin for ≥72 hours during 2008–2016 was conducted. Study patients were divided into three cohorts in accordance with their first trough levels at steady state: <5 mg/L (lower-trough), 5–10 mg/ L (low-trough), and >10 mg/L (high-trough; reference) cohorts. Results: Of the 201 patients eligible for study inclusion, 60 patients in the lower-and low-trough cohorts, respectively, were idect 3ntified via propensity score matching and analyzed against 30 high-trough patients in each comparison pair (neonates were excluded due to small sample size). Lower-trough patients were at a greater risk for prolonged therapy, retreatment, and dose adjustment than high-trough patients. Final steady-state troughs remained substantially lower in both the lower-and low-trough cohorts (p<0.001 and p=0.005, respectively), despite greater dose up-titration in the lower-trough cohort and percent change in daily dose in both the lower-and low-trough cohorts than in the high-trough cohort (p<0.001 for all). Clinical cure and death risk, along with the risks of isolation of resistant strains and renal events, were not significantly different between cohorts in both comparison pairs. Conclusion: Vancomycin troughs of <5 mg/L at initial steady state were associated with significantly compromised clinical outcomes in terms of risk of therapy prolongation, retreatment, and aggressive dose up-titration, compared to >10 mg/L troughs in pediatric patients with GPB infections.
Keywords: Drug monitoring; Gram-positive bacterial infection; Pediatrics; Vancomycin